A Case of Upper Ureter Rupture With Acute Kidney Injury. Issue 11 (25th June 2018) - Mutsuyoshi, Yuko; Kaneko, Shohei; Minato, Saori; Yanai, Katsunori; Ishii, Hiroki; Kitano, Taisuke; Shindo, Mitsutoshi; Miyazawa, Haruhisa; Ito, Kiyonori; Ueda, Yuichiro; Hirai, Keiji; Hoshino, Taro; et al.
We herein report a case of ureter rupture with severe oliguric acute renal injury due to benign prostatic hypertrophy. After insertion of an indwelling urinary catheter, the patient's urine output immediately increased. His symptoms and renal function also rapidly improved to the normal range without a surgical operation. Clinicians should note this complication in patients with oliguria.